2011
DOI: 10.1111/j.1570-7458.2011.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of male harassment on mating duration in the seed bug, Togo hemipterus

Abstract: Harassment on mating pairs by solitary males is usually considered an attempt by the male to (1) take over the female, (2) guard the female against further insemination (when the solitary male has previously copulated with this female), or (3) influence mating duration. Paired males of a seed bug repel harassment on mating pairs by solitary males by firmly grasping females using their legs and/or genital claspers; in this way, mating duration is prolonged. Male fertilization success increases as mating duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Similar conclusions were reached about competition between synthetic lures and wild females of the hemlock looper, Lambdina fiscellaria fiscellaria (Guenée) (Delisle et al, 1998). However, disruption of copulation can also occur due to the presence of too many males around a female hindering each others' efforts to reach her (Himuro & Fujisaki, 2012).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar conclusions were reached about competition between synthetic lures and wild females of the hemlock looper, Lambdina fiscellaria fiscellaria (Guenée) (Delisle et al, 1998). However, disruption of copulation can also occur due to the presence of too many males around a female hindering each others' efforts to reach her (Himuro & Fujisaki, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…We did not observe 100% mating success even at the highest population densities. However, disruption of copulation can also occur due to the presence of too many males around a female hindering each others' efforts to reach her (Himuro & Fujisaki, 2012). only about 86% of our females were receptive ( Figure 5).…”
Section: Discussionmentioning
confidence: 97%
“…Mate quality and number of mates are the key factor affecting female reproductive success (Bleu et al, 2012;Himuro & Fujisaki, 2012). Our mating interference experiments suggested that mating interactions between E. grisescens and E. obliqua were frequency-dependent.…”
Section: Discussionmentioning
confidence: 82%
“…In this sense, and considering that different modules perform distinct functions in copula (Genevcius and Schwertner 2017), we believe that sexual selection may have contrasting roles across modules. For example, male claspers are used as clasping devices and sometimes have been associated with a male's ability to prolong mating in the presence of other males (Moreno‐García and Cordero 2008; Himuro and Fujisaki 2012; Myers et al. 2016).…”
Section: Discussionmentioning
confidence: 99%